RANCANG BANGUN MESIN PERAJANG SINGKONG DENGAN SISTEM PENGATURAN KETEBALAN IRISAN DAN KECEPATAN - Yassin, Muhamad; Sunyoto, Sunyoto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The cassava chopper machine is one of the appropriate technologies used by small and medium enterprises. The results of the literature study and observation show that there are several issues, such as the ease of adjusting the thickness of the slices. The study aims to design a chopper machine equipped with slice thickness adjustment and speed control, with output measurements in the form of production capacity and slice quality. The method used in this research is the ADDIE (Analyze, Design, Development, Implementation and Evaluation) method. The specifications of the machine being made have dimensions 460x460x460 mm, with an electric motor driver (0.25 HP, 1400 rpm), a thickness variation of 0-2,5 mm, and two blades made of tungsten carbide. The results of this study show that the optimal thickness is 0.9 mm with speed adjustment in 1200 rpm. The capacity produced is 128.88 kg/hour with a slice quality of 90.49%.